The Effect Double Job of Audit Committee Member in Remuneration Committee on Audit Fees - Irsyad Fauzan Akbar , Ahmad; Firman Ramadhan, Adi (KnE Social Sciences, 2020)
The purpose of this study is to examine the effect of double job member of audit committee in remuneration committee on audit fees. This study refers to the Kalerkar (2012), by modifying the use of control variables and research samples. The dependent variables of this study is audit fees, the independent variable is double job in membership of audit committee at remuneration committee, this study also uses control variables to determine audit fees, there are audit risk, audit complexity, auditor characteristics, and audit committee characteristics. This study uses secondary data from annual reports and financial reports of all banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017. The research sample was taken by purposive sampling method. The total sample in this study is 41 companies. The analysis method used in this study is the multiple linear regression analysis. The results of this study indicate that double job in membership of audit committee at the remuneration committee negatively affects the price of audit fees. Keywords: Audit Fees, Audit Committee, Remuneration Committee, Double job member of audit committee in remuneration committee.